Investigation of thermomechanical properties and matrix-filler interaction on polyimide/graphene oxide composites - Mya, Khine Yi (2013)
We report, the preparation of nanocomposites having polyimide (PI) as matrix and graphene oxide (GO) as filler, analyses of matrix–filler interactions, and enhancements in thermomechanical properties of PI/GO as compared with pristine PI. The matrix–filler interactions were analyzed by 1H NMR, X-ray photoelectron spectroscopy, and density functional theory calculations. The data suggested stronger matrix–filler interactions in PI/GO as compared with PI/G composites. The stronger matrix–filler interactions and homogeneous dispersion of fillers lead to a significant enhancement in mechanical properties in PI/GO nanocomposites. Thus, with just 1 wt% GO content, the modulus of PI/GO composite increased by ∼106% as compared with pristine PI. Finally, thermal expansion coefficients of the nanocomposites are also investigated. A plausible hypothesis has been proposed in the text to explain the observed matrix–filler interactions and the subsequent property enhancements in nanocomposites.